2013
DOI: 10.1111/1365-2435.12178
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying variation among garden plants in attractiveness to bees and other flower‐visiting insects

Abstract: Summary1. Pollinating insects are globally declining, with one of the main causes being the loss of flowers. With the value of countryside reducing, urban areas, particularly gardens, are increasingly recognized as of benefit to wildlife, including flower-visiting insects. 2. Many gardeners specifically select plant varieties attractive to wildlife. Given the wide public interest, many lists of recommended varieties have been produced by both amateurs and professional organizations, but appear not to be well g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
197
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 191 publications
(217 citation statements)
references
References 41 publications
16
197
0
1
Order By: Relevance
“…Firstly, the number of immediately preceding visits to the same species that a particular visitor has made will potentially affect the amount of pollen it then deposits on the virgin flower we sampled; but there is no intrinsic reason (other than sheer floral density) why this influence will vary markedly amongst the various plants studied here, other than that some hybrid garden plants may have modified pollen amounts or accessibility compared to the native species (e.g. Garbuzov and Ratnieks 2014). Secondly, SVD records may be directly correlated with floral density, especially for bees, since multiple quick visits may move a greater percentage of the pollen from the pollinator's body onto the next flower, whereas in sparsely Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the number of immediately preceding visits to the same species that a particular visitor has made will potentially affect the amount of pollen it then deposits on the virgin flower we sampled; but there is no intrinsic reason (other than sheer floral density) why this influence will vary markedly amongst the various plants studied here, other than that some hybrid garden plants may have modified pollen amounts or accessibility compared to the native species (e.g. Garbuzov and Ratnieks 2014). Secondly, SVD records may be directly correlated with floral density, especially for bees, since multiple quick visits may move a greater percentage of the pollen from the pollinator's body onto the next flower, whereas in sparsely Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, cities can also provide new (foraging) habitat for animals (Paker et al 2014), and some studies revealed gardens, parks, and meadows as islands for insects (Gaston et al 2005a;Matteson et al 2008;Ahrné et al 2009;Garbuzov et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Forage flora consist of crop plants (Delaplane and Mayer, 2000) and wild species from natural and anthropogenically transformed communities (Wrzesień and Denisow, 2006;2007;Denisow, 2011). However, due to changes in crop structure and habitat loss or degradation, the value of countryside is decreasing but the value of urban areas, including ornamental gardens, is increasingly being recognized as an important source of food plants supporting a rich diversity of pollinators (Fussell and Corbet, 1992;Denisow and Bożek, 2006;Strzałkowska, 2006;Denisow, 2011;Garbuzov and Ratnieks, 2013). High flora diversity has been recorded among urban green spaces, such as parks, botanical gardens, private ornamental gardens, cemeteries, and railway areas; therefore, these areas are supportive to wild pollinators (Wrzesień and Denisow, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Because garden plants are often non-native, their usefulness for pollinator-friendly gardens requires observations of phenology, flowering biology and ecology, insect visitors, and the availability of floral reward (Denisow and Bożek, 2006;Strzałkowska, 2006;Masierowska, 2012;Denisow and Strzałkowska-Abramek, 2013). These studies are of great importance as the variation in the total number of insects attracted by ornamental species is broad (80-300-fold) (Garbuzov and Ratnieks, 2013). In Poland, the value of a floral reward from numerous ornamental herbaceous perennials, including species of the families Ranunculaceae, Saxifragaceae, and Malvaceae was highlighted by Denisow and Bożek (2006), Masierowska (2012), and Antoń and Denisow (2014).…”
mentioning
confidence: 99%